2011
DOI: 10.4314/afrrev.v5i2.67328
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Malaria Vectors in a Rainforest Suburban Community of Nigeria

Abstract: The ecology of malaria vectors in a suburban community of Umudioka, Dunukofia Local Government Area (LGA), Anambra State was studied between May and July 2009. Umudioka is an agrarian community in the rainforest zone of Nigeria and it is situated between longitude 6 0 85´E and Latitude 6 0 10´N of Equator. Mosquito larvae were collected from ground

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…By occupation, farmers and children of farmers had the highest prevalence (94.7%) while civil servants had the least prevalence of (65.4%).This agrees with Irikannu and Chukwuekezie [28] who also observed least prevalence among civil servants but contrasts with their findings where they observed highest prevalence in traders. Least malaria prevalence in civil servants has also been reported in Abagana [16]. Tshikuka et al [29] reported a similar relationship between occupation and malaria infection and observed a significantly higher prevalence of the Plasmodium parasite in low paid, unskilled workers and the unemployed than the civil servants.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…By occupation, farmers and children of farmers had the highest prevalence (94.7%) while civil servants had the least prevalence of (65.4%).This agrees with Irikannu and Chukwuekezie [28] who also observed least prevalence among civil servants but contrasts with their findings where they observed highest prevalence in traders. Least malaria prevalence in civil servants has also been reported in Abagana [16]. Tshikuka et al [29] reported a similar relationship between occupation and malaria infection and observed a significantly higher prevalence of the Plasmodium parasite in low paid, unskilled workers and the unemployed than the civil servants.…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence of malaria parasite in this study population is far higher than that of the following: 58.2% prevalence in Ogbunike, Anambra State [11], 38.9% prevalence in Awka, Anambra State [9]. It is also higher than 58.0% reported by Mbanugo and Ejims [7] in Awka, Anambra State, 46% prevalence in Nnewi, Anambra State [12], 27.29% prevalence in Sokoto, Sokoto State [13], 58.2% prevalence in Awka, Anambra State [14], 59.8% prevalence in Udi, Enugu State [15], 53.90% prevalence in Abagana, Anambra State [16], 76% in Azia, Anambra State [14], 74.9% prevalence in Yola, Adamawa State [17], 85.50% prevalence in Okigwe and 75% prevalence Owerri, Imo State [3], 73% prevalence in Ikwuano, Abia State [5] and 70.8% prevalence in Uli, Anambra State [9]. However, the results were lower than those of Kalu et al [18] who reported 93.3% in Aba and 90.39% prevalence in Umuahia in Abia State, and that of Ilozumba and Uzoezie [19] who reported 83.4% in Odoakpu in Onitsha South Local Government Area, Anambra State.…”
Section: Discussionmentioning
confidence: 99%
“…Three locations were selected for the study namely; Emelda hostel, Boys' hostel and Science village to reflect a range of landscapes encountered in the three regions all within Nnamdi Azikiwe University Awka located at the capital city of Anambra state which has a geographical coordinate of 612N and 704E, in the South Eastern zone of Nigeria (Onyido et al, 2011). It also has a minimum and a maximum average rainfall of about 7mm and 306mm respectively.…”
Section: Study Areamentioning
confidence: 99%
“…Several studies have elucidated the breeding behavior of vectors in different ecological settings [12][13]. The Knowledge about the bionomics of the vector species and their breeding site preferences are pre requisites for initiating long lasting larva source management of vector-borne diseases [14]. However, there is paucity of this information in Bayelsa State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%